Colossal current and voltage tunability in an organic memristor via electrode engineering. (June 2020) - Goswami, Sreetosh; Thompson, Damien; Williams, R. Stanley; Goswami, Sreebrata; Venkatesan, T.
Abstract: The physicochemical properties of a molecule-metal interface, in principle, can play a significant role in tuning the electronic properties of organic devices. In this report, we demonstrate an electrode engineering approach in a robust, reproducible molecular memristor that enables a colossal tunability in both switching voltage (from 130 mV to 4 V i.e. >2500% variation) and current (by ~6 orders of magnitude). This provides a spectrum of device design parameters that can be "dialed-in" to create fast, scalable and ultralow energy organic memristors optimal for applications spanning digital memory, logic circuits and brain-inspired computing. Graphical abstract: Image, graphical abstract